STRATEGI PENINGKATAN DAYA SAING PERUM BULOG - Suswono Suswono; Arief Daryanto; Mohamad Husein Sawit; Bustanul Arifin (Jurnal Manajemen & Agribisnis, 2009)
The objectives of this study is to examine the factors that affecting the adult in consuming enteral clinical nutrition products. Analysis knowledge and perception of doctors/dietician toward enteral clinical nutrition milk products and summarized marketing strategy that could be implemented in marketed enteral clinical nutrition milk products. This thesis also examine how the group reference can influence the adult in consuming enteral clinical products.  The study was conducted in five hospitals in Jakarta during February 2009. Total samples were 111 adults and 61 group references (doctors and dieticians).  Data were analyzed by using logit function.  The results indicated that the respondents, in consuming enteral clinical nutrition supplement, were influenced by doctors/ dieticians, education This research tries to explore the strategy to increase competitiveness of Perum BULOG after the status change. The goals of this research are to: 1) to analyse Perum BULOG's roles and function in the present and the future. 2) to analyse internal factors of Perum BULOG for increasing competitiveness; 3) to analyse policies needed for increasing competitiveness of Perum BULOG and 4) to formulate BULOG's strategy to increase competitiveness of Perum BULOG. This research was conducted using Analytic Network Process (ANP) method. The data were taken from relevant literatures (BULOG annual reports, textbooks, magazines, and relevant internet information), indepth interview, Focus Group Discussion (FGD), and experts panel. The research has shown that business PSO suggested by strong commitment of the government become priority function of Perum BULOG for five years to come; learning & growth as well as internal process aspect is the most important aspect. Value creation strategy is the best alternative strategy to increase BULOG's competitiveness. Keywords : Competitiveness, Perum BULOG, Analytic Network Process (ANP), Software Superdecisions